Indication of environmental changes in mountain catchments by dendroclimatology - Jiří VRTIŠKA; Josef KŘEČEK; Roberto TOGNETTI (Soil and Water Research, 2018)
In the Czech Republic, mountain watersheds are mostly forested with dominant Norway spruce (Picea abies) plantations. The aim of this paper is to analyse changes in radial growth and xylem anatomy of Norway spruce trees in the upper plain of the Jizera Mountains, related to changes in climate (air temperature, precipitation), air pollution and acid atmospheric deposition. Data of two neighbouring climate stations were used to detect trends in air temperatures and precipitation. At elevations of 745-1060 m a.s.l., the ring-width growth was significantly affected by mean annual temperature, while impacts of elevation and precipitation were not significant. In the period 1975-1995, the detected drop in tree radial growth (ca 60% of the normal period, prior to the peak of acid atmospheric deposition) corresponded to the increase in atmospheric SO2 concentrations and acid atmospheric deposition. The number of cells in tree rings decreased by ca 30-40% in comparison with the normal period, but the mean size of cells did not change significantly. In the last 20 years, increasing radial growth has been detected simultaneously with rising air temperature, and density of cells decreased by 30% in early wood, and by 10% in late wood, increasing the total number of cells in tree rings by ca 10% in comparison with the normal period. Integrated effects of climate and non-climate variables on the variation of tree radial growth in the Jizera Mountains reflected the legacy of acid atmospheric deposition in the forest ecosystem.